With Dreams in Our Hands: An African Feminist Framing of a Knowledge-Making Project with Former ESP Students - Knowles, Corinne (Education as Change, 2021)
This article introduces a research project that works with former Extended Studies Programme students to make knowledge that emerges through online, multimodal collaborations. Knowledge-making is not politically neutral, and the project and article are responding in part to the calls of the 2015/2016 South African student protesters to decolonise and transform university curricula. The project draws on African feminist ideas, emphasising the intersectional oppressions of colonialism, capitalism and patriarchy, which continue to influence theoretical choices in the knowledge hierarchies of South African and African universities. The “race”, class and gender inequalities that drive success or failure at university and in society become some of the topics addressed in the project, where former students as co-researchers collaborate to devise the topics, responses, and kinds of dissemination. Ntseane’s overlapping principles of a collective worldview, spirituality, a shared orientation to knowledge, and communal knowledge-making are motifs that influence how the project is imagined and run. My positionality as lead researcher and former lecturer of the co-researchers is navigated using African feminist guidance, which also informs the ethical principles of the project.